Pertumbuhan Riap Diameter Pohon Bakau Kurap (Rhizophora Mucronata) Di Lampung Mangrove Center - Kesuma, Robbi Angger; Kustanti, Asihing; Hilmanto, Rudi (Jurnal Sylva Lestari, 2016)
Bakau kurap (R. mucronata) is a true mangrove. The height of this mangrove could reach 27 m and rarely exceed 30 m. The diameter trunk of this mangrove could reach 70 cm. R. mucronata stands was found in Lampung Mangrove Center (LMC), it was located in Margasari Village district Labuhan Maringgai, East Lampung Regency. The purposes of this study were to determine the diameter increment, growth models and stand growth past of R. mucronata at LMC. The research was conducted on July to August 2015. The method used measurement of diameter time series for three years (2013, 2014, and 2015) on circle form permanent plots with a radius 7 m of length are divided into three thinning blocks (A, B, and C). Block C was the control block or block that was not thinned and large thinning in blocks A and B, respectively 54.5% and 41.7%. The results indicated that the biggest diameter increment of three block at the age of 22nd years = 0.467 cm year-1. The estimation model of stand diameter (D) and diameter increment (MAI-d) based on the age of stand (X) could be formulated as follows: 1) Blok A D = 8,996 X0,021; MAI-d = 0,451 X0,035, 2) Blok B D = 8,215 X0,124; MAI-d = 0,412 X0,039, 3) Blok C D = 7,159 X0,074; MAI-d = 0,359 X(-0,012). Forecasting growth stands diameter R. mucronata age of 32nd years on the blocks A, B and C in a row were 10,280cm, 9,463cm, and 7,796cm while the diameter increment were 0,467cm, 0,430cm, and 0,354cm. Key words : Diameter increment, forecasting, Lampung Mangrove Center, Rhizophora mucronata